2021
DOI: 10.18004/anales/2021.054.01.101
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Choledocholithiasis in patients with symptomatic gallstones treated in the II General Surgery Service of Clinica´s Hospital, San Lorenzo, year 2017-2019

Abstract: La litiasis vesicular sintomática puede presentarse asociada a litiasis de la vía biliar principal, siendo necesaria la utilización de medios diagnósticos adecuados para su posterior tratamiento. En este trabajo, se sugiere la evaluación mediante las guías de la Sociedad Americana para Endoscopia Gastrointestinal (American Society for Gastrointestinal Endoscopy ASGE), usando factores como la edad, pruebas hepáticas y hallazgos ecográficos, categorizando a los pacientes en baja, intermedia y alta probabilidad d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
2
0
1
Order By: Relevance
“…In the study performed by Machain G in 2021, choledochotomy with Kehr's drainage by open surgery was the most performed surgery done in patients submitted to surgery due to non-resolved BDS by ERCP (21 cases). (13) The main bias of the current study is the lack of long-term follow-ups, in order to corroborate subsequent clinical success. CONCLUSION 326 ERCP procedures were performed during the study, 245 were by suspicion of BDS, which was confirmed in 151 patients, giving a total of 38% of unnecessary ERCP (94 patients).…”
Section: Total 23mentioning
confidence: 88%
See 1 more Smart Citation
“…In the study performed by Machain G in 2021, choledochotomy with Kehr's drainage by open surgery was the most performed surgery done in patients submitted to surgery due to non-resolved BDS by ERCP (21 cases). (13) The main bias of the current study is the lack of long-term follow-ups, in order to corroborate subsequent clinical success. CONCLUSION 326 ERCP procedures were performed during the study, 245 were by suspicion of BDS, which was confirmed in 151 patients, giving a total of 38% of unnecessary ERCP (94 patients).…”
Section: Total 23mentioning
confidence: 88%
“…The low lithiasis finding percentage tells us that ERCP indication is not optimal, needing the utilized criteria to be evaluated; according to a study published by the Hospital de Clínicas (Asunción) in 2019, of the 40 patients submitted to ERCP due to BDS suspicion, calculi were reported in 21 of them (51%) numbers similar to the ones in the present work. (13) Since its implementation, ERCP has become an excellent technique for the preoperative study of the bile duct, with diagnostic sensibility and specificness close to 100%; it allows, through a side view endoscope, to cannulate the papilla and to opacify the bile duct injecting contrast. In this study, ERCP proved to be effective in 84% of BDS patients; according to a study published by Franco López J in 2021, endoscopic treatment's effectiveness was of 79.2% (14) Regarding the average age of the patients submitted to surgery (50 years old), it is similar to the one found in literature and other performed studies at national level; the greater prevalence in the female gender also matches the greater frequency of bile lithiasis presentation on said gender, being considered a risk factor for said pathology.…”
Section: Total 23mentioning
confidence: 99%
“…Mientras los electrolitos principales son el sodio, cloro y bicarbonato. (Machaín et al, 2021) Estos componentes deben mantener concentraciones equilibradas como explica el triángulo de Admirall-Small, el desbalance de los constituyentes llevan a la formación de los cálculos biliares en la vesícula y sumado a otros factores como la hipomotilidad vesicular, alteración de la lecitina constituyen la base fisiopatológica de la formación de los cálculos, Machaín et al (2021) indica en el caso de los cálculos pigmentarios existe una precipitación de la mucina y esta exacerba otros elementos como el fosfato cálcico y el bilirrubinato cálcico para la formación de los cálculos negros, mientras que en los marrones se involucran procesos de infección que alteran la característica de la bilis y lleva a la litogénesis. (Lammert et al, 2016) De acuerdo a las características macroscópicas y su composición química los cálculos biliares se dividen en aquellos que están formados por colesterol y pigmenta-…”
Section: Composición De La Bilisunclassified